The integration of rainwater harvesting facility into the house of Poblacion, Candijay, Bohol based on Type IV Philippine Climate Classification - Pascual, Myson Lloyd H. (College of Architecture, University of the Philippines Diliman, 2025)
Water scarcity is a significant concern worldwide. Despite falling under type IV climate classification, where rainfall is relatively evenly distributed throughout the year, Bohol still faces water scarcity in certain areas. One such area is Poblacion, Candijay, Bohol, where water shortages are most severe from March to May. The community's water supply primarily relies on wells and mountain springs. Although residents have implemented rainwater collection using pails, barrels and drums, this system remains inadequate and insufficient to meet their non-potable water demands. To address this issue, the study aims to explore how to integrate rainwater harvesting into the initial house designs. It examines 40 houses in Poblacion as a reference for building technology styles and practices, as well as water demand within the community. The study utilized recent precipitation data from PAGASA along with water consumption data obtained from surveys to determine the minimum roof size and tank capacity. Furthermore, systematic observations and considerations of building technology and materials were considered in the design transformation process. The study found that the roof area is directly proportional to the amount of water collected and inversely proportional to the level of precipitation. The findings indicate that roof area significantly affects water collection, and the design must consider the month with the least rainfall to ensure adequacy. Tank dimensions should correspond to monthly consumption and average excess rainwater to maximize collection. In developing the models, the study uses factors derived from the survey questions answered by the largest number of participants. These factors include user profiles, monthly water consumption, and the predominant architectural styles of houses within the community. These models show that rainwater harvesting can be effectively incorporated into the initial design of residential buildings with careful consideration of the aforementioned factors. The study promotes sustainability by incorporating rainwater harvesting facilities, making it a vital component of contemporary building practices that transform residential designs into more relevant and climate-responsive architecture.